Interrelationship of community and community-based enterprises: A case of cooperatives in Hue, Viet Nam - Khanh Hung Doan; Thi Nhung Tran (CTU Journal of Innovation and Sustainable Development)
Communities play a significant role in stimulating entrepreneurship and contributing substantially to promoting, connecting, and cooperating in developing entrepreneurship and local development. However, the connection between communities and entrepreneurship remains a multifaceted topic that is not easily defined or fully understood. While certain studies have acknowledged how communities can encourage entrepreneurial activity by leveraging various aspects of their structure and culture, a thorough and comprehensive examination of the community’s overall role and impact on entrepreneurship is still lacking. This article presents the roles and relationships between communities and community-based enterprises (CBE). Using qualitative interviews, the study investigates community-based enterprise managers’ perceptions of the community role in CBE development. The results show that there is a significant difference in the perception of the community's role in the CBE and the local development of the interviewees. Additionally, the coordination and contributions of the community to CBE are also different. Despite the differences, it is important to note that communities all have a role to play in entrepreneurship and local development. This study emphasizes the importance of community development research to foster and encourage future CBE. This knowledge can inform strategies for community and CBE development.